Efeitos do laser sobre as alterações bioquímicas e morfológicas induzidas por um modelo de lesão cutânea em ratos - Hartmann, Diane Duarte (2015)
Skin ulcer is a condition that can lead to serious complications, when not treated. Among the resources used to treat skin lesions is the low level laser therapy (LLLT), is extensively studied in the literature, wich could accelerate tissue healing. Thus, this study aims to evaluate the effects of LLLT on the hematological changes and biochemical alterations in the skin, such as oxidative stress, antioxidant capacity, mitochondrial dehydrogenase activity and morphological changes induced by a skin injury model in rats, made through the instrument surgical "punch". For these studies were used 70 Wistar rats that were divided into Control, Sham, Lesion and Lesion+LLLT groups. The biochemical and morphological experimental analyzes were performed at different times in 1st, 3rd, 7th, 14th, 21st day after the development of injury from skin tissue samples and blood sample in order to investigate the chronological development of the well lesions how to check the effectiveness of laser therapy used. Lesion+LLLT group showed an increase in total number of leukocytes, reduced DCF levels in comparison to values observed in 1 day and reduced the TBARS levels in 7th to 21th days, when compared to control group. The MTT reduction levels and NPSH levels were increased in the 1st day after skin injury with treatment group. Considering data the LLLT accelerated skin tissue repair in a mechanism that involves increases of ROS production at early stages of tissue healing.